DUCKWEED (LEMNA MINOR) AS FEED INGREDIENT FOR FINGERLINGS OF COMMON CARP (CYPRINUS CARPIO) - GHOSH, T. K.; PAUL, B. K.; CHATTOPADHYAY, D. N.; MANDAL, R. N. (Journal of the Inland Fisheries Society of India, 2021)
Inclusion of quality protein in preparation of fish feed is essential for obtaining optimal fish growth. Duckweed a cheap protein source of plant origin was tested as ingredient for preparation of fish feed. To look into its protein quality, an experiment was carried out with incorporation of duckweed (Lemna minor) as an ingredient in fish feed (F1 : duckweed, 85% + rice bran, 15%) as compared to other two different fish feeds having costly ingredients (F2 : mustard oil cake, 78% + rice bran, 22% and F3 : ground nut oil cake, 88% + rice bran, 12%) so as to evaluate their efficacy. Three feeds (F1 , F2 and F3 ) were fed to fry of common carp (Cyprinus carpio) for a period of 90 days. Growth parameters such as weight gain, average daily weight gain (ADG) and final body weight of common carp fry feeding on F1 exhibited significantly (p< 0.05) higher values than that of fry feeding on F2 and F3 . Further, common carp feeding on F1 performed better growth in respect of FCR and SGR as compared to F2 and F3 feeds.This experiment suggests that duckweed (Lemna minor) may be incorporated as an ingredient of quality protein source for preparation of fish feed to be used for feeding of common carp fry during its rearing. The inclusion of duckweed will certainly reduce the feed cost and also improve the growth as well as health of fry. Key words: Common carp fry, duckweed, fish feed, growth, ingredients, protein